(untitled) (Research, Society and Development, 2022)
Introduction: Chronic endometritis (EC) is a disease of continuous inflammation caused by bacterial pathogens such as Enterobacteriaceae, Enterococcus, Streptococcus, Staphylococcus, Mycoplasma and Ureaplasma. In addition to being poorly investigated, it can be found in up to 40% of infertile patients. EC has been linked to adverse reproductive outcomes such as repeated implantation failure (RIF) and recurrent miscarriage. Objective: The objective of our study is to evaluate the impact of antibiotic treatment on the obstetric prognosis of patients. Methodology: This is a literature review on the use of antibiotics as therapy for chronic endometritis, elaborated through consultations in the main scientific databases. Results: Patients with cured chronic endometritis had a higher pregnancy rate and live birth rate compared to women with persistent disease. In this bias, current studies show that treatment with oral antibiotics against EC may be a promising therapeutic option for infertile women with RIF. Conclusion: It is concluded that antibiotic treatment improves RIF and decreases the miscarriage rate, although they have a failure rate of 10% and there is a lack of well-designed prospective studies that corroborate this finding. Finally, research on associations with corticosteroids and local administration is necessary, as some studies have brought positive results.